lncRNA HIF1A Antisense RNA 2 Modulates Trophoblast Cell Invasion and Proliferation through Upregulating PHLDA1 Expression - Wu, Dan (Mol Ther Nucleic Acids, 2019)
Long noncoding RNAs (lncRNAs) have been reported to be involved in various human diseases, and increasing studies have revealed that lncRNAs can play a vital role in preeclampsia (PE). In our study, lncRNA hypoxia-inducible factor 1 alpha (HIF1A) antisense RNA 2 (HIF1A-AS2) was found to be significantly downregulated in placenta tissues of PE patients by quantitative real-time PCR analysis. Moreover, Cell Counting Kit-8 (CCK-8) assays showed that downregulation of HIF1A-AS2 can impede cell proliferation of HTR-8/SVneo and JAR trophoblasts cells. Ectopic overexpression of HIF1A-AS2 can increase the function of trophoblasts cell migration and invasion in vitro. RNA-sequencing (RNA-seq), RNA immunoprecipitation (RIP), and chromatin immunoprecipitation (ChIP) experiments showed that HIF1A-AS2 can recruit lysine-specific demethylase 1 (LSD1) and epigenetically repress pleckstrin homology-like domain, family A, member 1 (PHLDA1) transcription in human trophoblasts cells. In summary, our findings suggest that downregulated HIF1A-AS2 may play a role in the pathogenesis and progression of PE, and has potential as a novel prognostic marker in PE.